The TIR Domain Containing Locus of Enterococcus faecalis Is Predominant among Urinary Tract Infection Isolates and Downregulates Host Inflammatory Response - Kraemer, Thomas Daniel (Hindawi Publishing Corporation, 2014)
Based on Toll/interleukin-1 receptor (TIR) domain structure homology, we detected a previously uncharacterized gene encoding for a TIR domain containing protein (Tcp) in the genome of Enterococcus faecalis. We assigned this gene the name tcpF (as in Tcp of E. faecalis). Screening of E. faecalis samples revealed that tcpF is more common in isolates from urinary tract infections (UTIs) than in human faecal flora. tcpF alleles showed moderate single nucleotide polymorphism (SNP) among UTI isolates. Infection of mouse RAW264.7 macrophages with a tcpF knock-out mutant led to elevated cytokine response compared to the isogenic wild type E. faecalis strain. In silico analysis predicted significant tertiary structure homology to the TIR domain of human TLR1 (TLR1-TIR). When transiently expressed in cultured eukaryotic cells, TcpF caused suppression of TLR2-dependent NF-κB activation suggesting for TcpF a role as a factor in E. faecalis that benefits colonization by modulating the host's immune responses.